Installation of retaining wall at 3 storey house at Tanjung Bungah / Mohd Izham Mohd Zin - Mohd Zin, Mohd Izham (Universiti Teknologi MARA, Perak, 2013)
This report will describes about the installation of retaining wall at Tanjung Bungah, Penang. all the procedure and equipment, and any related method must be apply on that site. Other than that there are few types of retaining wall which have different used. Retaining wall is a part of structure at this site because the soil condition that nearby the hill is so dangerous if they do not use this structure. We as a client and developer need to supervise on that site to avoid failure or bad thing.